2019
DOI: 10.31557/apjcp.2019.20.4.1139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HER2 Expression and Its Correlation with Clinicopathological Parameters in Gastric or Gastroesophageal Junction Adenocarcinoma in North-East Indian Population

Abstract: Gastric cancer is a leading health-care problem worldwide and is the fifth most common cancer in the world, with 952,000 new cases diagnosed in 2012 Worldwide 0.7 million people die of gastric cancer each year (accounts for 8.8% of all cancer-related deaths) [GLOBACON, 2012]. Gastric cancer is the second most common cancer among men and third-most among females in Asia (Rahman et al., 2014) and is the second most common cause of cancer-related deaths in India (Dikshit et al., 2012). A high incidence of gastric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
2
11
0
2
Order By: Relevance
“…Motoshima et al discovered Her2 in 14.5 percent of the patients they investigated. In sum, 56 percent (n=38) of the 68 individuals investigated by Roy et al, [29] had HER2 positive test findings. In a separate analysis, Panigrahi et al [30] discovered that 26.92 percent (21 cases) were positive for Her2, 16.67 percent (13 cases) were equivocal, and 56.41 percent (44 cases) were negative.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Motoshima et al discovered Her2 in 14.5 percent of the patients they investigated. In sum, 56 percent (n=38) of the 68 individuals investigated by Roy et al, [29] had HER2 positive test findings. In a separate analysis, Panigrahi et al [30] discovered that 26.92 percent (21 cases) were positive for Her2, 16.67 percent (13 cases) were equivocal, and 56.41 percent (44 cases) were negative.…”
Section: Discussionmentioning
confidence: 77%
“…Phan et al [31] discovered that 26.6 percent of male and 20.3 percent of female patients have HER2. Roy et al [29] confirmed that Her2 was positive in 66% of males and 36% of females with no statistical significance. Positive incidences accounted for 5% of persons above the age of 50 in our study.…”
Section: Discussionmentioning
confidence: 97%
“…It has been confirmed that 12–35% of gastric cancers have HER2 overexpression, and HER2 is an independent prognostic factor of gastric cancer [ 21 ]. The results of Roy et al [ 22 ] showed that HER2 protein expression in patients with gastric cancer combined with lymph node metastasis was significantly higher than that in those without lymph node metastasis; HER2 protein expression in patients with infiltration reaching beyond the serosa was significantly higher than in those with infiltration within the serosa, and HER2 protein in lymph node metastasis of gastric cancer was highly expressed. Patients with HER2-positive tumors had poorer prognosis and lower 5-year survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…With the change of scoring criteria and the de nition of oesophagogastric junction adenocarcinoma, the HER2-amplication rate exhibits a great discrepancy, which varies with an extremely wide range, from 4-53% (median, 20.2%) [11,12]. Previous studies showed that HER2-positivity rate was higher in oesophagogastric junction than gastric adenocarcinoma [13,14], while some studies suggested that the presence of HER2-expression was not associated with tumor location [15,16]. HER2-expression is heterogeneous in gastric or oesophagogastric junction adenocarcinoma, thus it's important to review the HER2 status and its correlating clinicopathological features according to the V5.0.…”
Section: Introductionmentioning
confidence: 99%